Association of Neutrophil–Lymphocyte Ratio With the Presence and Severity of Rheumatic Mitral Valve Stenosis. (November 2014) - Polat, Nihat; Yildiz, Abdulkadir; Yuksel, Murat; Bilik, Mehmet Zihni; Aydin, Mesut; Acet, Halit; Akil, Mehmet Ata; Oylumlu, Mustafa; Kaya, Hasan; Ertas, Faruk; Cil, Habib
The aim of the study is to investigate the association between the severity of rheumatic mitral valvular disease (RMVD) and the neutrophil–lymphocyte ratio (NLR). A total of 227 patients were enrolled in the study and divided into 3 groups. Patients in group 1 had rheumatic mitral stenosis (RMS), those in group 2 had RMVD without stenosis, and those in group 3 served as the control group. Group 1 was further divided into 2 groups, severe mitral stenosis (MS) and mild to moderate MS. The NLR was significantly higher in patients with severe MS when compared to those with mild to moderate MS ( P = .002) while lymphocyte count was lower ( P = .034). Using a cutoff level of 2.56, the NLR predicted severe RMS with a sensitivity of 75% and specificity of 74%. In conclusion, as an inexpensive, simple, and accessible marker of inflammation, the NLR may be useful in predicting the presence and severity of MS in patients with RMVD.